Gold(I)-Catalyzed Synthesis of Polycyclic Frameworks Related to Terpenes: Selective Divergent Synthesis of Fused Carbocycles - Barabe, Francis (Université d'Ottawa / University of Ottawa, 2013)
Gold catalysis has become an important tool to achieve highly chemoselective p-acid activation. Exceptional reactivity and selectivity are often encountered under mild reaction conditions. These properties have made gold(I) complexes suitable catalysts for tremendous applications in the total synthesis of natural products. The first chapter will highlight a number of total syntheses using gold catalysis as a key step. The second chapter will cover our application of the gold(I)-catalyzed 6-endo-dig carbocyclization for the synthesis of bridgehead-substituted scaffolds and its use toward the synthesis of PPAP natural products. This research has opened our eyes to the utility of biphenylphosphine ligands, particularly JohnPhos, in gold(I)-catalysis. The reactivity and selectivity exhibited by gold(I) complexes is modulated by the nature of the ancillary ligand. Recent research rationalizes the impact of these ligands on the divergent reactivity observed between cationic and carbenoid intermediates. Our desire to favor the 6-endo-dig pathway has led us toward the discovery of another example of the diagonal reactivity that NHC carbene and biphenylphosphine ligands can bring to gold(I)-catalysis. Chapter three will explain the development of a selective gold-catalyzed synthesis of fused carbocycles . Our selective divergent synthesis of fused carbocycles, combined with the Diels–Alder reaction, has brought new synthetic opportunities. Chapter four will describe our approach toward the synthesis of various polycyclic diterpene-related frameworks. Starting with a unique linear precursor, we have developed a new “one-pot” process for the synthesis of three different polycyclic compounds related to the terpenoid family. The facile modulation of the linear precursor and the use of different dienophiles during the Diels–Alder reaction could enable the synthesis of diverse polycyclic analogues based on three principal frameworks. The gold(I)-catalyzed synthesis of fused carbocycles reached some limitations during our study. Regioselective control was found to be substantially more challenging, with terminal alkynes or alkynes bearing a sterically and electronically neutral methyl substituent. In chapter five, we will discuss how the complementarity of silver(I) catalysis to gold(I) catalysis enabled the selective divergent synthesis of three different fused carbocycles from a unique precursor. Moreover, copper(I) catalysis has given access to the 6-endo-dig pathway on terminal alkynes without the formation of a vinylidene intermediate.
Keywords: gold(I)-catalysis; carbocyclization; fused carbocycles; bridged carbocycles; PPAP natural product; silver(I)-catalysis; copper(I)-catalysis; tandem reaction